A multi-hop D2D and social awareness based novel relay selection algorithm - Liang LI; Xinjie YANG (Dianxin kexue)
The social domain was introduced to multi-hop D2D (device-to-device) communication in cellular network scenarios, and a novel relay selection algorithm for multi-hop D2D communication under cellular network was proposed.Unlike existing relay selection algorithms, the proposed algorithm selects relays for each hop in reverse order, which reduces the signaling overhead caused by algorithm implement.Then, social domain information of mobile terminals was introduced to the algorithm and its influence on the algorithm’s performance was studied, which was found significant enough not to be overlooked hence providing useful guidance to designing algorithms in practical systems.Moreover, via extensive Monte Carlo simulations, it is discovered that the proposed algorithm outperforms the benchmarks in terms of data throughput and energy efficiency in absence of social relationship information.In a more practical implementation with social relationship information included, the proposed algorithm though naturally achieving less throughput, significantly outperforms the benchmarks in energy efficiency.